Paideia and Self-Fashioning in Ammianus Marcellinus - Sánchez-Vendramini, Dario N. (Histos, 2016)
In many passages of the Res Gestae, Ammianus criticizes contemporary individuals and groups that lack a literary culture befitting their rank. These passages were commonly interpreted as a reflection of Ammianus’ class prejudices. In contrast, the main thesis of this paper is that Ammianus’ perspective on paideia can also be seen as part of the self-fashioning strategy deployed in his work. Ammianus establishes almost a direct equivalence between the possession of paideia and elite membership. In criticizing the ignorance of emperors, officials, and aristocrats, Ammianus is indirectly asserting his own superiority, not only in the intellectual field but also in the social sphere. Throughout his work, Ammianus does not spare any effort to convince his readers of his erudition and literary culture, constructing for himself the identity of a Greek intellectual. Name-dropping and the digressive style he employs in the Res Gestae constitute the main means to construct this identity, because they allow Ammianus to display his encyclopedic learning in a way not common in historical works.